2019
DOI: 10.3758/s13414-019-01729-0
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic features of fragrances: The role of grammatical gender and gender associations

Abstract: Odors are often difficult to identify and name, which leaves them vulnerable to the influence of language. The present study tests the boundaries of the effect of language on odor cognition by examining the effect of grammatical gender. We presented participants with male and female fragrances paired with descriptions of masculine or feminine grammatical gender. In Experiment 1 we found that memory for fragrances was enhanced when the grammatical gender of a fragrance description matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 78 publications
0
13
1
Order By: Relevance
“…Similarly, Poupon et al (2019) found that within 2 months of training, student sommeliers had improved odor naming abilities, but showed no corresponding improvement in odor memory, suggesting these two expert skills are unrelated. Evidence suggests that mental simulation of odor—automatically activating olfactory representations during language comprehension—is difficult (Speed & Majid, 2018; Speed & Majid, 2019b). Evidence also indicates that conscious odor images—that is, an active odor representation without the presence of the actual odor—are particularly difficult to evoke from language (Stevenson & Case, 2005; Stevenson, Case, & Mahmut, 2007; Stevenson & Mahmut, 2013), possibly more difficult than imagery in other modalities (cf., Arshamian & Larsson, 2014; Arshamian, Olofsson, Jönsson, & Larsson, 2008).…”
Section: Evidence That Odor Naming Does Not Enhances Odor Memory Func...mentioning
confidence: 99%
“…Similarly, Poupon et al (2019) found that within 2 months of training, student sommeliers had improved odor naming abilities, but showed no corresponding improvement in odor memory, suggesting these two expert skills are unrelated. Evidence suggests that mental simulation of odor—automatically activating olfactory representations during language comprehension—is difficult (Speed & Majid, 2018; Speed & Majid, 2019b). Evidence also indicates that conscious odor images—that is, an active odor representation without the presence of the actual odor—are particularly difficult to evoke from language (Stevenson & Case, 2005; Stevenson, Case, & Mahmut, 2007; Stevenson & Mahmut, 2013), possibly more difficult than imagery in other modalities (cf., Arshamian & Larsson, 2014; Arshamian, Olofsson, Jönsson, & Larsson, 2008).…”
Section: Evidence That Odor Naming Does Not Enhances Odor Memory Func...mentioning
confidence: 99%
“…For example, when asked to describe an object, Spanish and German speakers are more likely to ascribe stereotypically male qualities to objects with masculine grammatical gender, and stereotypically female qualities to objects with feminine grammatical gender (Boroditsky, Schmidt, & Phillips, 2003; but see Mickan, Schiefke, & Stefanowitsch, 2014). Grammatical gender can even affect the way people remember complex fragrances: fragrances are remembered better when the grammatical gender of ingredients in the fragrance match the gender of the person the fragrance is marketed towards (Speed & Majid, 2019).…”
Section: Classifiers Rflect Conceptual Structurementioning
confidence: 99%
“…Studies across a number of different disciplines such as chemoreception (e.g., Bensafi, Rinck, Schaal, & Rouby, 2007;White & Prescott, 2007), food science (e.g., Soufflet, Calonnier, & Dacremont, 2004;Zampini, Sanabria, Phillips, & Spence, 2007), psychology (e.g., Raudenbush, Meyer, Eppich, Corley, & Petterson, 2002;Ren, Tan, Arriaga, & Chan, 2015), and consumer research (e.g., Lowrey, Lerman, & Luna, 2007;Lowrey & Shrum, 2007) have shown that congruent multisensory experience is preferred over incongruent multisensory experience. Studies involving recall tests and identification tasks, for example, show that congruent stimuli are more memorable (e.g., Preziosi & Coane, 2017;Speed & Majid, 2019) and more recognizable (e.g., Lupyan & Ward, 2013;Reiner, Hetch, Helevy, & Furman, 2006) than incongruent stimuli. Furthermore, visual attention is enhanced through congruent stimuli such as sounds (e.g., Dolscheid, Hunnius, Casasanto, & Majid, 2014;Knoeferle, Knoeferle, Velasco, & Spence, 2016) and odors (e.g., Robinson, Mattingley, & Reinhard, 2013;Seo, Roidl, Müller, & Negoias, 2010).…”
Section: Enhancing Sensory Experiencementioning
confidence: 99%